2018
DOI: 10.3389/fmicb.2018.01544
|View full text |Cite
|
Sign up to set email alerts
|

The Immune Protection Induced by a Serine Protease Inhibitor From the Foodborne Parasite Trichinella spiralis

Abstract: Serine protease inhibitors (SPI) are a superfamily of the proteins able to suppress serine protease activity, and may exert the major biological function in complement activation, inflammation, and fibrinolysis. A SPI was identified from Trichinella spiralis adult worms (AW) by immunoproteomics with early infection sera. The aim of this study was to investigate the protective immune elicited by TsSPI. The complete TsSPI cDNA sequence was cloned into pQE-80 L and then expressed in Escherichia coli BL21. The rTs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
46
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 50 publications
(46 citation statements)
references
References 81 publications
0
46
0
Order By: Relevance
“…The characteristics of the TsEla gene were analyzed using bioanalysis software [39]. The tertiary structure and functional site of TsEla protein was predicted using PyMOL and CN3D software [40]. TsEla amino acid sequences were compared with elastases from other organisms by means of Clustal X [41].…”
Section: Bioinformatics Analysis Of Tselamentioning
confidence: 99%
“…The characteristics of the TsEla gene were analyzed using bioanalysis software [39]. The tertiary structure and functional site of TsEla protein was predicted using PyMOL and CN3D software [40]. TsEla amino acid sequences were compared with elastases from other organisms by means of Clustal X [41].…”
Section: Bioinformatics Analysis Of Tselamentioning
confidence: 99%
“…Quantitative PCR (qPCR) and immunofluorescence assay revealed that the TsSPI gene was highly expressed at enteral stage worms (AW and NBL), principally located in the cuticle and stichosome of this nematode. Vaccination of mice with rTsSPI produced a 62.2% intestinal AW reduction and a 57.25% ML reduction after larval challenge [ 19 ]. The aim of this study was to investigate the biological characteristics of TsSPI and its roles in the course of T. spiralis invasion of host’s IECs.…”
Section: Introductionmentioning
confidence: 99%
“…In future studies, polyvalent vaccines should be developed and contain multiple protective antigenic epitopes from diverse T. spiralis developmental phases (IIL, AW, NBL and ML) to elicit both systemic/ enteral local humoral and cellular immune responses. To acquire full immune protection, ideal polyvalent vaccines must prevent Trichinella infection and block the development of clinical trichinellosis at various lifecycle phases: interrupting IIL larval invasion of enteral epithelia, blocking IIL larval development to the adult stage, dislodging adult worms from the guts, interdicting or impeding NBL generation from enteral residual adults, killing escaping NBL to prevent their migration in blood and larval encapsulation in skeletal muscles [36,69]. Hence, oral polyvalent vaccines against different T. spiralis life cycle phases need to be developed to interrupt Trichinella infection transmission among domestic food animals [9].…”
Section: Discussionmentioning
confidence: 99%
“…Serum levels of anti-rTsE antibodies (total IgG, IgG1, IgG2a, and IgA) in all vaccinated mice were tested by ELISA with rTsE [35,36]. Briefly, the ELISA plate was coated using 1 μg/mL rTsE for total IgG and 2 μg/mL rTsE for IgG1, IgG2a and IgA at 37 °C for 2 h. Skimmed milk at a 5% concentration was used for blocking at 37 °C for 1 h. Different dilutions of mouse sera (1:100 for detecting IgG, IgG1 and IgG2a; 1:50 for detecting IgA) were added and incubated at 37 °C for 2 h. Following washes with TBS-0.5% Tween 20 (TBST), 1:10 000 dilutions of HRP-conjugated anti-mouse IgG, IgG1 or IgG2a, and 1:5000 dilutions of HRP-conjugated anti-mouse IgA were added and incubated for 1 h at 37 °C [37].…”
Section: Detection Of Antibody Responses To Rtsementioning
confidence: 99%